The relationship between non-HDL-C/HDL-C ratio and bone mineral density: an NHANES study - Qi, Shuo; Peng, Biao; Xu, Zhanwang; Qiu, Daodi; Tan, Guoqing (Frontiers in Nutrition, 2025)
BackgroundThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a newly developed lipid parameter. However, the current research has only explored the relationship with lumbar spine bone mineral density, lacking studies on bone mineral density at other sites, total body bone mineral density, and an analysis of risk factors. This study aims to determine the potential association between NHHR and lumbar BMD, increase awareness of the impact of lipid levels on bone health.MethodsBy utilizing data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018, we conducted univariate and generalized linear models (GLMs) analysis, stratified analysis, threshold effect analysis, smooth curve fitting and stratified analysis to investigate the association between NHHR and BMD. NHHR levels were categorized into tertiles (low, medium, and high) based on their distribution among the study population.ResultsThe study included 8,671participants, studies have shown, the ratio of non-high-density lipoprotein to high-density lipoprotein (NHHR) exhibits a stratified correlation with bone mineral density (BMD). In the BMI subgroup, NHHR is significantly negatively correlated with BMD at multiple sites in the low-to-middle BMI group (BMI <25 kg/m2), while no significant correlation is found in the high BMI group (BMI ≥30 kg/m2). In the gender subgroup, NHHR has a more pronounced effect on male BMD, mainly reflected in the reduction of lumbar spine and total body BMD. In the age subgroup, the negative correlation between NHHR and BMD is strongest in the younger group (18–30 years), gradually weakening in the middle-aged (31–44 years) and older groups (45–59 years). Further analysis suggests that dyslipidemia may influence bone metabolism through pathways such as inflammation and oxidative stress.ConclusionThe effect of NHHR on bone mineral density (BMD) varies by BMI, gender, and age. This study suggests that controlling NHHR levels may be a potential intervention target for bone health management, particularly for individuals with low-to-middle BMI, males, and younger populations. These findings offer a new perspective on the relationship between lipid metabolism and bone metabolism and provide scientific evidence for the development of personalized osteoporosis prevention and treatment strategies.